VIRTUAL REALITY SEBAGAI PENGINDUKSIAN EMOSI NEGATIF DI INDONESIA - Ali, Fachry; Grasiaswaty, Novika; Triman, Arif (Mediapsi, 2021)
Emotion is the driving motive of life for humans. The induction of emotions is necessary to understand the behavioural effects and neurobiological determinants of human emotions. The goal of the present work was to examine the effectiveness of virtual reality as a tool to induce negative emotions among a sample of Indonesian participants (N = 20, with the age ranging between 18 and 25 years old). Emotional manipulation in this research used the immersive video watching method to induce negative emotions, which was measured using the emotional baseline scale. Â The finding revealed that among the five negative emotions tested, virtual reality significantly induced anger. What can be implied from this finding is that virtual reality can be of use as a reference for the immersive video database in emotion induction research.Emosi merupakan motif penggerak kehidupan bagi manusia. Penginduksian emosi diperlukan untuk memahami efek perilaku dan penentu neurobiologis emosi manusia. Penelitian ini bertujuan menguji keefektifan virtual reality sebagai alat menginduksi emosi negatif pada responden di Indonesia. Partisipan penelitian berjumlah 20 mahasiswa dengan Â rentang usia 18-25 tahun. Manipulasi emosi dalam penelitian ini menggunakan metode menonton video immersive untuk menginduksi emosi negatif yang diukur dengan skala emotional baseline. Hasil penelitian menunjukkan bahwa virtual reality secara signikan mampu menginduksi emosi marah dari lima emosi negatif yang diuji. Implikasinya, virtual reality dapat dijadikan sebagai suatu rujukan database video immersive dalam penelitian penginduksian emosi.